1958
DOI: 10.4039/ent9081-2
|View full text |Cite
|
Sign up to set email alerts
|

The Olfactory Guidance of Flying Insects

Abstract: The use of olfactory repellents, especially against biting insects, is an important protective measure. It is also a matter of common knowledge that certain insects are able to locate their mates or their prey largely through the agency of attractive scents. Concerning these latter, Dethier remarks that, “we recognize the fact that no one attractant alone performs the service of guiding an organism to its proper habitat, or mate, or food. The desired end is achieved by a complex array of stimuli working in har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(76 citation statements)
references
References 6 publications
1
74
0
1
Order By: Relevance
“…Therefore, it was suggested that it is in this shifting maze that the insect must find the active space containing those few signals that will lead it to its host plant. However, in the open air, it is turbulence rather than diffusion that determines the distribution of odorous molecules (Wright, 1958;Bossert & Wilson, 1963), and there is nearly always a prevailing wind to blow the odorous molecules away from the plant. Registering directional cues from odorous molecules is even more complicated for flying insects, as the movement of the air relative to the insect depends on the insect's own activity, and wind direction has to be registered in the absence of fixed markers (Finch, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was suggested that it is in this shifting maze that the insect must find the active space containing those few signals that will lead it to its host plant. However, in the open air, it is turbulence rather than diffusion that determines the distribution of odorous molecules (Wright, 1958;Bossert & Wilson, 1963), and there is nearly always a prevailing wind to blow the odorous molecules away from the plant. Registering directional cues from odorous molecules is even more complicated for flying insects, as the movement of the air relative to the insect depends on the insect's own activity, and wind direction has to be registered in the absence of fixed markers (Finch, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Turbulence causes the plume to break up into strands of odor-laden air (filaments) interspersed with pockets of clean air where little or no odor is present (11,12). The physical intermittency of these filaments is a requirement for male moths to sustain their upwind progress; they will not continue to fly upwind upon entering a homogeneous cloud of pheromone (4, 13) but will if this cloud is alternated with swaths of clean air (14).…”
Section: Introductionmentioning
confidence: 99%
“…The 'zigzagging' paths of insects orientating to distant odour sources have long been a matter for study (Wright, 1958;Farkas & Shorey, 1972;Kennedy & Marsh, 1974). Such paths are most commonly observed in male moths flying upwind to sources of female sex pheromone (Kennedy, 1983).…”
Section: Introductionmentioning
confidence: 99%